Geopolitik dan geostrategi indonesia dalam menghadapi tantangan global untuk memperkuat kedaulatan dan keberlanjutan nasional - romadhon, ilham nur (Maliki Interdisciplinary Journal, 2025)
This journal discusses the importance of geopolitics and national identity in maintaining the unity of the Republic of Indonesia. Indonesia’s geopolitical perspective is reflected in the concept of Wawasan Nusantara, which views the entire Indonesian territory as an integrated whole. Meanwhile, national identity serves as a unifying force that strengthens the nation’s sense of togetherness. Issues in border areas, such as poverty and uneven development, highlight the need for practical implementation of Wawasan Nusantara. National security can no longer be viewed solely through a military lens but must also address social, economic, and cultural dimensions. This paper recommends strengthening civic education, ensuring equitable development in border regions, and enhancing cooperation between central and local governments to safeguard national sovereignty and unity amid global challenges.